Ensino e aprendizagem de química a partir da temática “tintas para tatuagem” - Calderan, Arlete Pierina (2017)
This master's degree research aims to favor the teaching and learning of Chemistry through the contextualization of the scientific contents with the theme "inks for tattoo", for high school students of a Public School of Santa Maria, RS. It presents a qualitative approach, based on a methodology of Action research. Initially a bibliographic research was performed on "inks for tattoo", the teaching of Chemistry, the use of thematic and methodologies of teaching of Sciences/Chemistry, such as thematic workshops, experimental activities and case studies. The research was developed in two stages: in Step I, two investigative questionnaires with open questions were applied, one to tattoo artists and the other to tattooed people, in order to investigate whether they consider important to know the chemical composition of tattoo inks and the use of Personal Protective Equipment (PPE). In addition to being a didactic strategy the obtained information brought elements that helped in the development of Stage II of the research with the students, and the activities developed in 10 (ten) Interventions, the first one with the presentation of the theme, the following 8 (eight) inserted in two Thematic Workshops (TW), the last one (10ª) focused on the closing of the activities, totalizing 26 hours/class. In the first TW, titled "Chemistry of Solutions and Inks for Tattoo", the priority was given to reviewing contents of 1st and 2nd years of high school, such as solubility, polarity, intermolecular interactions, oxidation-reduction, inorganic functions and metal ions. In the second TW, titled "Organic Chemistry and Inks for tattoo" contemplated contents of Organic Chemistry. These contents were contextualized with the everyday and with the theme "inks for tattoo", besides being performed multidisciplinary approaches. For data collection, instruments such as questionnaires, textual productions, exercises and systematic observations were used and analyzed according to the Discursive Textual Analysis (DTA). The students interacted in a group created in the WhatsApp Messenger application, in order to also discuss the Socio-Scientific Issues (SSI), during the resolution of a proposed case. The results showed that the theme of "inks for tattoo", along with different teaching methodologies allowed students to make important associations between scientific, thematic and daily contents; favoring meaningful learning.